Modeling cognitive thinking style of schoolchildren in the system of advanced education for sustainable development (Actual Problems of Psychology in Educational Institutions, 2018)
The article is devoted to the analysis of the problem ofsustainable development as the basis of the meaningful life choice of a person inthe unstable conditions of socio-cultural reformation of civilization. It isemphasized that education is an integral part of the universal phenomenon ofdevelopment, the main priority of sustainable development of society. Theauthor emphasizes that the application of the integrative (centrist) model ofsustainable development allows to expand the scope of education, to fill it witha personal meaning. In the plane of the above, the peculiarities of thedevelopment of the cognitive thinking style of pupils of teenage ages areanalyzed. The conclusion is made on the necessity of purposeful escort of thisprocess in the conditions of sustainable development education.
Keywords: sustainable development, education, cognitive thinking, teenage age